Disorder and coercivity in magnetic particle systems - Zhao, Yang (2011)
Computer simulation has been utilized to understand the hysteretic behavior of magnetic particle systems. Particles are assumed to be single domain, spherical in shape, and possess no intrinsic anisotropy. Neighboring spins are not exchange-coupled. Particles are either randomly packed or displaced from cubic lattice positions in random directions. The gyromagnetic equation of motion with Landau-Lifshitz damping is solved for each spin during a dynamic process. Regular spin arrangements yield no hysteresis or coercivity. For spin configurations randomly displaced from a cubic lattice, hysteretic behavior is observed. Coercivity increases with randomness of particle position. Detailed examination of the magnetization reversals reveals chain formations and transient vortex states in randomly packed arrays. Coercivity versus packing fraction inferred for finite sized particles shows a maximum.